Overcoming risk for women in leader identity development. Issue 1 (26th October 2020) - Ryan, Nuala F.; Hammond, Michelle; MacCurtain, Sarah; Cross, Christine
Abstract : Purpose: The purpose of this paper is to advance our understanding of the role of risk in leader identity development for women by identifying processes women leaders employ to overcome perceived risk. Design/methodology/approach: Twenty-five women leaders in the Irish healthcare sector took part in an 18-month long identity-based leadership development program. Qualitative data from interviews, focus groups, critical incident diaries and individual exit surveys and observations were analyzed using the constant comparative method. Findings: Four key processes are identified as women leaders work through risks associated with structural elements (perceiving and mitigating structural risk) and agency of the leader (accepting agentic risks and developing agency). Research limitations/implications: Like many focused qualitative studies, generalizability to a larger population might be limited. The authors, therefore, recommend future research to consider these issues in other industries, levels and national contexts. Practical implications: Organizational members should pay attention to structural factors that affect women's perceptions of risks in internalizing a leader identity such as perceptions of organizational support for development, role models, mentoring and behavioral norms. Programs should aim to increase individual agency through personal reflection and freedom to experiment. Originality/value: This paper offers an original and nuanced perspective on the role of risk in the leader identity development process for women.